The Origin, Intricate Nature, and Role of the Skin Surface pH (pHSS) in Barrier Integrity, Eczema, and Psoriasis - Dalibor Mijaljica; Joshua P. Townley; Daniel J. Klionsky; Fabrizio Spada; Mikayla Lai (Cosmetics)
The inherent acidic nature of the stratum corneum (SC), the so-called “acid mantle”, has a multitude of effects on skin barrier integrity owing to its (patho)physiological role in skin homeostasis, antimicrobial defense, and inflammation. Several salient SC acidifying mechanisms, including the breakdown of FLG (filaggrin) protein, lipid processing, and the activity of the sodium proton pump SLC9A1/NHE1, are indispensable for the structural and functional integrity and cohesion of the SC as they contribute immensely to the origin, generation, maintenance, and overall SC acidification of the skin surface pH (pHss). As many endogenous and exogenous factors can affect the pHss, the pHss can inevitably deviate from its optimum. The elevation of the pHss is often accompanied by abnormalities in SC lipid metabolism and organization, SC cohesion, and SC integrity and is commonly observed in eczema, which is associated with symptoms of dry skin, inflammation, pruritus, and infection. In psoriasis, it seems that the pHss is altered as well; however, in this case, it is likely to be lower than the physiological pHss. Due to the negative effects of an altered pHss in both eczema and psoriasis, it has been suggested to maintain the pHss at physiological levels by utilizing pH-balanced topical cleansers and moisturizers that can improve the skin’s structural and functional integrity by benefiting skin moisturization and the regeneration and organization of the SC barrier. The principal aim of this review is to gather an understanding of the existing research and to stimulate critical thinking and inspire innovative ideas about ‘known unknowns’, considering the origin, intricate nature, and prime role of the pHss in human skin health, as well as the pathogenesis of eczema and psoriasis.